2016
DOI: 10.1371/journal.pone.0150552
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 1 (IGF-1) in Parkinson's Disease: Potential as Trait-, Progression- and Prediction Marker and Confounding Factors

Abstract: IntroductionBiomarkers indicating trait, progression and prediction of pathology and symptoms in Parkinson's disease (PD) often lack specificity or reliability. Investigating biomarker variance between individuals and over time and the effect of confounding factors is essential for the evaluation of biomarkers in PD, such as insulin-like growth factor 1 (IGF-1).Materials and MethodsIGF-1 serum levels were investigated in up to 8 biannual visits in 37 PD patients and 22 healthy controls (HC) in the longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 52 publications
1
22
1
Order By: Relevance
“…These IGF-1 concentrations inversely correlate with the UPDRS-III score (i.e. with motor function), verbal episodic memory, visuoperceptual abilities and attention/ executive functions; been not found such correlation on healthy subjects [171][172][173][174][175][176][177][178][179][180][181]. As it has been shown, lower IGF-1 levels at the beginning of PD are associated with a worse disease progression and prognosis.…”
Section: Theoretical Relationship Between Parkinson's Disease and Igfmentioning
confidence: 85%
“…These IGF-1 concentrations inversely correlate with the UPDRS-III score (i.e. with motor function), verbal episodic memory, visuoperceptual abilities and attention/ executive functions; been not found such correlation on healthy subjects [171][172][173][174][175][176][177][178][179][180][181]. As it has been shown, lower IGF-1 levels at the beginning of PD are associated with a worse disease progression and prognosis.…”
Section: Theoretical Relationship Between Parkinson's Disease and Igfmentioning
confidence: 85%
“…Even gastric and colonic mucosa have been profiled for markers (Chung et al, 2016). Blood is probably the most active area of PD marker research looking at a range of potential targets from IGF-I titers (Bernhard et al, 2016), micro-RNA signatures (Ding et al, 2016), mitochondrial densities (Pyle et al, 2016), vitamins (Ding et al, 2013; Ide et al, 2015), lymphocytes (Tan et al, 2014, 2016) and proteins like alpha-synuclein (SNCA) (Pihlstrøm et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…While serum and plasma levels offer a potential biomarker of brain Mn dysregulation, further studies must examine how these levels correlate to what is seen in actual brain tissue. Studies have found that changes in IGF by age, sex, diet, BMI, and secondary disease status can cause immense variability between patients, particularly in peripheral samples 118 . Several heavy metals are reported to accumulate in the brain with age and can differ by similar confounds suggesting peripheral Mn may also be an inappropriate measurement for brain Mn.…”
Section: Discussionmentioning
confidence: 99%